Tinjauan Yuridis Tentang Penyelesaian Sengketa Pemutusan Hubungan Kerja di Perusahaan Badan Hukum (Studi Kasus Putusan Nomor 68/Pdt.Sus-Phi/2023/Pn Mdn) - Saragih, Yuni Sari; Isnaini, Isnaini; Hidayani, Sri (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article or paper aims to analyze the Dispute Resolution of Industrial Relations Disputes Between Employees and Employers in Indonesia and analyze the Judge's Considerations in Deciding Industrial Relations Disputes Between Employees and PT. Tor Ganda Based on Decision Number 68/Pdt.Sus-PHI/2023/PN Mdn. This study uses a normative juridical method with analysis of primary and secondary legal materials to evaluate the resolution of industrial relations disputes and judges' considerations in Decision Number 68/Pdt.Sus-PHI/2023/PN Mdn. Qualitative analysis is carried out to understand the application of labor law and the protection of workers' rights. The results of the study show that the settlement of industrial relations disputes in Indonesia is carried out through bipartite, tripartite, and PHI mechanisms per the law. The case of PT. The Double Tor reflects violations of workers' rights, including wages and social security. The judge declared the layoffs invalid and ordered the payment of compensation. This ruling emphasizes the importance of clear work documentation and the company's compliance with the rules, to create fair industrial relations.